İlk Dönem Tasavvuf Kültüründe Horasan Melâmîliği ve Anadolu'da Bir Melâmî Karakter: Zembilfroş - Özsoy, Naci (Muş Alparslan Üniversitesi, 2014)
Bu çalışmada, Horasan Melamîliği, gelişimi, üstadları, prensipleri araştırılacak. İmam Gazâlî’nin melâmî tavrı, sûfîlere yönelik eleştirileri irdelenecek. Horasan Melamî düşüncesinin Anadolu’yu nasıl etkilediği incelenecek. Ayrıca Zembilfroş karakterinin Horasan Melamîliğinden nasıl etkilenmiş olabileceği ve aralarındaki benzerlikler ortaya konulacaktır.

In this study, Khorasan Melamis, its evolution, its masters and principles will be investigated. Imam Ghazali’s Melami attitude and his criticism against the sufis will be analyzed. It wil be examined how the idea of Khorasan Melamis affected the Anatolia. And also It will be put forth how the Zembilfrosh character could be affected from Khorasan Melamîs and similarities between them.
Khorasan Melamis and a Melami Character in Anatolia in the First Period of Sufi Culture: Zembilfrosh
anemon
Keywords: Zühd; Tasavvuf; Melâmî; Horasan Melâmîliği; İmam Gazâlî; Zembilfroş; Asceticism; Sufism; Melami; Khorasan Dervishes; Ghazali; Zembilfrosh